Science, philosophy and physical geography - Inkpen, Robert, 1964- (Routledge, 2013)
This accessible and engaging text explores the relationship between philosophy, science and physical geography. It addresses an imbalance that exists in opinion, teaching and to a lesser extent research, between a philosophically enriched human geography and a perceived philosophically empty physical geography. The text challenges the myth that there is a single self-evident scientific method that can, and is, applied in a straightforward manner by physical geographers. It demonstrates the variety of alternative philosophical perspectives and emphasizes the difference that the real wo.